IGNITING CURRENT TRENDS IN TEACHING THROUGH THE INTEGRATION OF SOCIAL MEDIA IN ECONOMICS EDUCATION (International Journal of Innovative Technologies in Economy, 2025)
Social media (SM) has become an omnipresent force in the lives of learners, teachers, and academic institutions worldwide. As digital platforms like Facebook, Twitter, Instagram, LinkedIn, and TikTok continue to evolve, they are increasingly being integrated into the educational sphere. This paper explores the potential of SM in economics education, reviewing the existing literature on its effectiveness in enhancing learner engagement, understanding, and learning outcomes. The researcher identifies best practices for integrating SM into economics curricula and discusses the challenges and limitations associated with its use. The data collection process involved searching for relevant scholarly articles using Scopus, ResearchGate, and Google Scholar from 2020 to 2024. A systematic review of literature on the role of social media (SM) in education was conducted using the PRISMA 2020 framework. The study included 45 peer-reviewed articles selected for comprehensive analysis. These articles encompassed a diverse range of contexts, including urban, rural, and international education systems. The systematic literature review for this study used thematic content analysis to examine a range of pertinent literature sources. Emerging from the analysis were the following themes, namely enhanced student engagement, improved understanding, real-time data analysis, collaborative learning, information overload, distractions, the digital divide, and intellectual property concerns. The study found that some teachers ban the use of mobile devices because they distract learners from learning, while learners believe that mobile SM enhances communication with peers and instructors. The study recommends that an ICT policy must be in place to manage and control SM for effective adoption.